Ответы и объяснения

2014-04-06T22:23:35+04:00
1)  3^{-3} *  3^{5} =  3^{2} = 9
 5^{-2} :  5^{-3} = 5

2)  \frac{ a^{5} * a^{2}}{ a^{-3}} =  \frac{ a^{3}}{ a^{-3}} =  a^{6}
 (x^{2} ) ^{-3} *  x^{4} =  x^{-6} *  x^{4} =  x^{-2}

3)  \frac{ 6^{-3} * 2^{-4} }{ 18^{-2}} =  \frac{ 18^{-7}}{ 18^{-2}} =  1^{-5} = -1

4) ([tex]( a^{-1} + b^{-1} )^2 - 4 a^{-1} b^{-1} = a^{-2} + 2 a^{-1} b^{-1} + b^{-2} - 4 a^{-1} b^{-1}= a^{-2}+ 2 a^{-1} b^{-1}+ b^{-2} =(a+b) ^{-2}




а дальше нету случайно ...:)
дальнейшее решение добавлю позже
продолжение 4 задания
(1/2000 + 1/1999)^-2 = (2000 + 1999)^2 = 4000000 + 3996001 = 7996000000
((x-y) / (x+y) - (x+y) / (x-y))^-1 : ((x^2 - y^2) / 2y * (2x)^-1) =
= ((x+y) / (x-y) - (x-y) / (x+y)) : ((x^2 - y^2) / 2y * 1/2x) =
= ((x+y)*(x+y) - (x-y)*(x-y) / (x+y) * (x-y)) : ((x^2 - y^2) / 4xy) =
= ((x^2 + 2xy + y^2) - (x^2 - 2xy + y^2) /( x^2 - 2xy +y^2)) * (4xy / (x^2 - y^2)) =
= (x^2 + 2xy + y^2 - x^2 + 2xy - y^2) / (x^2 - 2xy +y^2)) * (4xy / (x^2 - y^2)) =
= (4xy / (x^2-y^2)) * (4xy / (x^2 - y^2)) =
= 16x^2y^ / (x^4 - x^2y^2 - x^2y^2 +y^4) =
= 16x^2y^ / (x^4 - 2x^2y^2 + y^4)